Defining the Functional Targets of Cap'n'collar Transcription Factors NRF1, NRF2, and NRF3 - Lara Ibrahim; Jaleh Mesgarzadeh; Ian Xu; Evan T. Powers; R. Luke Wiseman; Michael J. Bollong (MDPI AG, 2020)
The NRF transcription factors NRF1, NRF2, and NRF3, are a subset of Cap'n'collar transcriptional regulators which modulate the expression of genes harboring antioxidant-response element (ARE) sequences within their genomic loci. Despite the emerging physiological importance of NRF family members, the repertoire of their genetic targets remains incompletely defined. Here we use RNA-sequencing-based transcriptional profiling and quantitative proteomics to delineate the overlapping and differential genetic programs effected by the three NRF transcription factors. We then create consensus target gene sets regulated by NRF1, NRF2, and NRF3 and define the integrity of these gene sets for probing NRF activity in mammalian cell culture and human tissues. Together, our data provide a quantitative assessment of how NRF family members sculpt proteomes and transcriptomes, providing a framework to understand the critical physiological importance of NRF transcription factors and to establish pharmacologic approaches for therapeutically activating these transcriptional programs in disease.